Do Financial Items Determined Using Estimates and/or Professional Judgment Adhere to Benford’s Law of First Digits? - Jordan, Charles E.; Clark, Stanley J. (Journal of Applied Business and Economics, 2022)
Among other things, Benford’s Law provides the rates at which the numerals one through nine should materialize as the first digit of naturally occurring figures and is often used as an analytical tool for identifying suspicious data sets. Yet, recent research in Romania suggests Benford’s Law does not hold for financial statement items whose determination requires extensive use of estimates and/or professional judgment (e.g., depreciation expense or revenue) and, accordingly, should not be used for evaluating such items. The current article reports on similar research conducted in the U.S. and shows that all financial items examined, including those requiring significant use of estimates and/or professional judgment, conform to Benford’s Law.